Dual-Frequency Miniaturized Substrate Integrated Waveguide Quarter-Mode Cavity-Backed Antenna Based on Minkowski Fractal Gap with Orthogonal Polarization Radiation Characteristics - Zihao Fu; Tianliang Zhang; You Lan; Tianhai Wu; Wenxing Huang; Leilei He (International Journal of Antennas and Propagation)
A novel quarter-mode substrate integrated waveguide miniaturized cavity-backed antenna loading Minkowski fractal gap is presented in this paper. Firstly, the resonant frequency of the rectangular substrate integrated waveguide resonator is reduced by etching the fractal gap in the resonator to achieve miniaturization. In addition, because of the symmetry of electric field distribution in second and third order resonant modes, the cavity can be segmented into a quarter-mode and the other order resonance modes with asymmetric electric field distribution can be suppressed according to the cavity model theory. Hence, the cavity size is further reduced. The dimension of designed antenna is 0.26λ0×0.26λ0 (λ0 is the wavelength in free space; in this paper, the corresponding wavelength is 3.6 GHz). Moreover, the orthogonal polarization of the proposed antenna in two frequency bands is achieved because the electric field is orthogonal in second and third order resonant modes. This dual-frequency orthogonal polarization characteristic enables antenna to communicate in two working bands and has good channel isolation. The simulated and measured results are consistent. The antenna gain is 4.67dBi and 3.4dBi, respectively, at 3.7GHz and 4.6GHz.